Indización por materias en repositorios digitales: Una incursión en la producción científica brasileña sobre ciencia de la información - Tartarotti, Roberta Cristina Dal Evedove; Dal’ Evedove, Paula Regina [UNESP]; Fujita, Mariângela Spotti Lopes (My University, 2020)
Subject indexing in digital repositories is surveyed in the Brazilian scientific production of Information Science. In conclusion, it is verified that although the upward relevance of digital repositories, and more presently of the institutional repositories, is currently a reality in the academic field, research in the field of Knowledge Organization that specifically cover the subject indexing in digital repositories are still incipient.
Indexação em repositórios digitais: Uma incursão na produção científica brasileira de ciência da informação
Keywords: Brazil; Digital repositories; Information science; Scientific production; Subject indexing